Anatomical variations of nasal and paranasal sinuses among Sudanese patients undergoing CT scan evaluation at Antalya Diagnostic Center – Khartoum – Sudan, 2017 - Mohamed, Mohamed Gubriel; Osman, Wail N; Nurain, Mohammed A Alsalam; Mohamed, Mohamed Elsiddig (Gezira Journal of Health Sciences, 2022)
Introduction: The anatomical variations of the paranasal sinus are common among populations. These variations are asymptomatic most of the time, yet it may be associated with some inflammatory or allergic conditions. Knowledge of these anatomic variations helps in choosing the operative techniques, reducing the surgical complication rates and explains recurrence of disease. Objective: The aim of this study was to investigate the incidence and type of the anatomical variations of the paranasal sinus among adult Sudanese population by using CT scan. Patients and Method: This is a retrospective descriptive and health facility-based study, conducted at Antalya Diagnostic Center, Khartoum, during the period from July to September 2017. Included in the study all patients referred to the center for CT scan of the sinuses (n=151). A simple random technique was used for anatomical variations; with a sample size of 76 patients. Data collection sheet was used included demographic data and the anatomical variations. Data was analyzed using SPSS version 22. Results: The total number of patients diagnosed with variations was 76, which constituted of 50.3% of all patients included in the study. The age of patients ranged between 16 to 65 years, with a mean age of 36.46 (±11.12SD) years. The most frequent age groups were (16 to 25) and (26 to 35) years which constituted (52.63%) of the patients. Males were 34 (44.7%) and females were 42 (55.3%), with a male to female ratio 1:1.23. Relationship between age and gender with anatomical variants was found not statistically significant. Ninety variations were detected among the study sample. Nasal septal deviation was the commonest variation observed in (26.7%), followed by Concha bullosa in (20%), Onodi Cells in (11.1%), Agger nasi in  (10%), frontal sinus hypoplasia in  (10%) and other variations in ( 22.2%) of cases. Most of the variants were unilateral (81.6%) and were more on the left side in (46.1%) of cases. Conclusions and recommendations: the commonest variation was Nasal septal deviation, variations were common among the age group 16 to 35 years with slight female predominance. The study emphasizes the importance of CT scan for the detection of anatomical variations of the paranasal sinus in every patients planned for nasal or sinus surgery.